2017
DOI: 10.1371/journal.pone.0183044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating quality management systems for HIV rapid testing services in primary healthcare clinics in rural KwaZulu-Natal, South Africa

Abstract: IntroductionRapid HIV tests have improved access to HIV diagnosis and treatment by providing quick and convenient testing in rural clinics and resource-limited settings. In this study, we evaluated the quality management system for voluntary and provider-initiated point-of-care HIV testing in primary healthcare (PHC) clinics in rural KwaZulu-Natal (KZN), South Africa.Material and methodsWe conducted a quality assessment audit in eleven PHC clinics that offer voluntary HIV testing and counselling in rural KZN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 29 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…21 The evaluation study showed that there is poor quality supply chain management and poor adherence to standards among staff in rural PHC clinics. 21 These findings are also supported by Mbachu et al, 29 Pavie et al 30 and Moodley et al, 31 who showed the accuracy of HIV rapid testing services in resource-limited settings. To ensure sustainable accuracy of the HIV rapid test services provided, it is important that evidence-based guidelines are followed, particularly in high HIV-prevalence regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The evaluation study showed that there is poor quality supply chain management and poor adherence to standards among staff in rural PHC clinics. 21 These findings are also supported by Mbachu et al, 29 Pavie et al 30 and Moodley et al, 31 who showed the accuracy of HIV rapid testing services in resource-limited settings. To ensure sustainable accuracy of the HIV rapid test services provided, it is important that evidence-based guidelines are followed, particularly in high HIV-prevalence regions.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel study was conducted to access quality systems management for HIV rapid testing services in rural KZN. 21 …”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With continuous advances in technologies for prevention and treatment of HIV and TB, continuous professional development (CPD) of health care workers (HCWs) remains a high priority especially, in countries with a dual burden of TB/HIV epidemics (Feldacker et al, 2017;Wirtz et al, 2016). The World Health Organisation (WHO) recommends training and competency assessments for personnel, including initial and follow up trainings as components of a quality management system (QMS) necessary for provision of quality POC diagnostic services (Jaya, Drain, & Mashamba-Thompson, 2017). Studies have been conducted to evaluate compliance to the QMS in LMIC, specifically on HIV and TB testing in South Africa (Jaya et al, 2017;Mwisongo, Peltzer, Mohlabane, & Tutshana, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organisation (WHO) recommends training and competency assessments for personnel, including initial and follow up trainings as components of a quality management system (QMS) necessary for provision of quality POC diagnostic services (Jaya, Drain, & Mashamba-Thompson, 2017). Studies have been conducted to evaluate compliance to the QMS in LMIC, specifically on HIV and TB testing in South Africa (Jaya et al, 2017;Mwisongo, Peltzer, Mohlabane, & Tutshana, 2016). These studies highlighted knowledge gaps and barriers to the provision of quality services in resource limited settings, which include challenges concerning test user perspectives and competency (Jaya et al, 2017;Mwisongo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%